The Roles of Magnetorheological Fluid in Modern Precision Machining Field: A Review - Lu, He; Hua, Dezheng; Wang, Baiyi; Yang, Chengli; Hnydiuk-Stefan, Anna; Królczyk, Grzegorz; Liu, Xinhua; Li, Zhixiong (Frontiers in Materials, 2021)
Owing to some of its specific advantages, magnetorheological fluid (MRF) has drawn significant attention in a broad range of modern precision machining fields. With the diversification and increase in demand, many novel structural configurations and processing methods have been applied to mechanical machining equipment. Although different applications using MRF have been proposed in the existing literature, the classification, latest approaches, and further trend are not understood clearly for the machining field. Therefore, the current applications such as machining auxiliary equipment and surface polishing equipment that used MRF are summarized from 2016 to 2020, in this article. Especially, some detailed structures of equipment are investigated, and relative limitations are analyzed based on the characteristics of MRF. Finally, in view of the current equipment, advantages and defects are briefly reported; the developing trends of modern precision machining with MRF are discussed. Therefore, in the state-of-the-art review, the significant role of MRF in the machining field is emphasized, which paves the way to innovative development and market selection.